Treatment Feasibility of NSSC Pulping Effl uent using UASB Reactor - Ali, Arshad; Hashmi, Hashim Nisar; Querashi, Inthikhab Ahmad; Saeed, Athar (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
The safe disposal of black liquor generating from Neutral Sulfide Semi-Chemical pulping section of the paper mills is one of the challenging issue in the developing countries. A treatment feasibility study was conducted on a laboratory scale UASB (Upflow Anaerobic Sludge Blanket) reactor running on continuous flow basis for about 30 weeks at neutral pH and at constant temperature of 33°C. It is observed that about 35% of black-liquor COD could be reduced at a hydraulic retention time of 38 hours and at an organic loading rate of 2.75 kg-COD/m3-day. The average gas production and methane gas conversion at optimum conditions was observed to be 0.17 m3/kg-CODrem-day and 0.88 L-CH4/g-CODrem-day, respectively. The overall methane composition was noticed to be 61% of the biogas. This study suggests that the post-treatment of NSSC pulping effl uent is required to meet the safe effl uent disposal standards. Key words: NSSC pulping; UASB; Anaerobic digestion; Lignin-COD; Pakistan DOI: 10.3126/hn.v5i0.2489 Hydro Nepal Vol. 5, July 2009 Page:46-49